Local Allergic Rhinitis to Pollens is Underdiagnosed in Young Patients. Issue 6 (September 2016) - Krajewska-Wojtys, Anna; Jarzab, Jerzy; Gawlik, Radoslaw; Bozek, Andrzej
Background: Local allergic rhinitis (LAR) has been observed in patients without atopy. However, LAR is still underdiagnosed in patients with perennial or seasonal nasal symptoms. Objective: The aim of this study was to determine the prevalence of LAR in young patients with a previous diagnosis of nonallergic rhinitis or suspicion of allergy. Methods: A total of 121 patients, ages 12–18 years old, with confirmed nonallergic rhinitis and typical seasonal nasal symptoms were examined. Skin-prick tests; serum and nasal specific immunoglobulin E (IgE) measurements; and nasal provocation tests by using grass (Phleum partense), Artemisia, and birch pollens were performed. A control group of age-matched patients with a diagnosis of seasonal allergic rhinitis underwent the same procedures as the test group. Results: LAR to grass pollen (P. partense), Artemisia, and birch was confirmed in 17 (16.6%), 6 (5.9%), and 9 (8.9%) of patients, respectively. Polyvalent allergy was established in 21 subjects (20.8%): grass and Artemisia, 11 patients (10.9%); and grass and birch, 10 patients (9.9%). The remaining 48 patients (47.5%) were diagnosed with nonallergic rhinitis. The results of the nasal provocation tests and the concentrations of nasal IgE were similar among the analyzed groups. Furthermore, the concentration of nasal IgE increased faster in patients with LAR than in patients with allergic rhinitis; however, this difference was not statistically significant. Conclusion: LAR is a serious problem in young patients; however, its significance is still unappreciated.